Digital natives vs. digital immigrants? – szkoła a kreatywność online - Przybyła, Mariusz (Wydawnictwo Naukowe UAM, 2012)
The article is an attempt to outline the changes that have occurred in a vacuum existing between an institutionalized school and digitally enthusiastic students/pupils. The functioning of education members and the institutional framework of education itself within a net society is a vital issue, which the article analyses from a cognitive and practical viewpoint. The article presents the profi le of a contemporary student/pupil at different times of his or her educational journey. The article moreover attempts to present alarming questions regarding the effectiveness and attractiveness of school, which actually functions side by side with the Internet. Moreover, the text emphasizes the problem of a digital gap between the technologically-advanced youth (digital natives) and teachers, parents, tutors – digital immigrants. Strange as it may seem in this context, school – the most conservative, also cognitively, educative institution that seems to perpetuate the above division, feels responsible for guarding the gates of the digital world. The article is also an important contribution to the discussion on the Internet which, to a certain extent, has freed education from its frozen structures. As a result education and us have received a multidimensional exchange of information, thoughts and experience. In addition, the author raises other important issues such as individualization, a creative use of the global net and creativity on-line.
Digital Natives vs. Digital Immigrants? School and On-line Creativity
Keywords: digital gap; digital immigrants; digital natives; creativity on-line; individualization